Antibacterial Activity of Lactic Acid Bacteria Isolated from Cincalok Against Escherichia coli and Listeria monocytogenes - Oktavia, Yulia; Lubis, Zuwita Cahaya Rani Br; Amrizal, Sri Novalina; Wulandari, Wulandari (Program Pascasarjana Universitas Sriwijaya, 2025)
This study aims to determine the antibacterial activity of lactic acid bacteria (LAB) isolates from cincalok, a traditional shrimp fermentation product, against Escherichia coli and Listeria monocytogenes. Five lactic acid bacteria isolates (A1, A2, A3, A4, and A5) were assayed for their antagonistic activity against E. coli and L. monocytogenes. The antagonistic assays were conducted with different incubation times of the LAB isolates before the antagonistic assays. The incubation times were 18, 21, and 24 hours. LAB isolates that showed inhibition zones were further assayed in antibacterial assays. Antibacterial assays were conducted by the disk diffusion method. Antagonistic and antibacterial assays were each carried out in triplicate. The antagonistic assay results showed that only isolates A3 and A4, which were incubated for 24 hours, showed inhibition zones. Inhibition zones of isolate A3 against L. monocytogenes were 1.33 ± 1.04 mm, while against E. coli were 0.67 ± 0.29 mm. Inhibition zones of isolate A4 against L. monocytogenes were 1.33 ± 1.04 mm, while against E. coli were 1 ± 0.5 mm. Antibacterial assay results showed inhibition zones of isolate A3 against L. monocytogenes were 4.67 ± 0.58 mm, while E. coli 6.67 ± 2.08 mm. Inhibition zones of isolate A4 against L. monocytogenes were 3.67 ± 0.58 mm, while E. coli 4.33 ± 0.58 mm. Antibacterial activity of Isolates A3 and A4 had weak inhibition against L. monocytogenes and E. coli. Antibacterial activity depended on the type of target bacteria and was influenced by incubation time and environmental conditions.